1999
DOI: 10.1021/jp9847080
|View full text |Cite
|
Sign up to set email alerts
|

Ion Beam Induced Crosslinking Reactions in Poly(di-n-hexylsilane)

Abstract: Thin solid films of poly(di-n-hexylsilane) were irradiated with a variety of high-energy ion beams, electron beams, and 60 Co γ-rays of which linear energy transfer (LET) ranges from 0.2 to 1620 eV/nm. The beams caused nonhomogeneous reactions of crosslinking and main chain scission in the films. The molecular weight of the polymer was traced to give the efficiency of crosslinking reactions: G(x) based on the CharlesbyPinner relationship. The value of G(x) increases from 0.042 to 0.91 with increasing values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 36 publications
(67 reference statements)
2
37
0
Order By: Relevance
“…The threshold for the dominance of one over the other process was found to be at proton energies of 20-25 MeV, corresponding to a stopping power of approximately 3 eV/nm. This value is comparable to the findings of a previous study of poly(di-nhexylsilane) where a threshold value of 10 eV/nm was reported [30]. Although this scenario qualitatively fits the experimental observations and is in agreement with concepts reported in the literature, several uncertainties remain.…”
Section: Radiation-induced Degradation In Polymerssupporting
confidence: 91%
See 1 more Smart Citation
“…The threshold for the dominance of one over the other process was found to be at proton energies of 20-25 MeV, corresponding to a stopping power of approximately 3 eV/nm. This value is comparable to the findings of a previous study of poly(di-nhexylsilane) where a threshold value of 10 eV/nm was reported [30]. Although this scenario qualitatively fits the experimental observations and is in agreement with concepts reported in the literature, several uncertainties remain.…”
Section: Radiation-induced Degradation In Polymerssupporting
confidence: 91%
“…The LET describes the energy loss from the perspective of the particle, whereas the stopping power is a measure of the energy absorbed by the material. LET-dependent radiation effects, in which the observed damage is correlated to the electronic stopping power of the radiation, were investigated in various polymers including aromatic and aliphatic compounds [23], [25], [27], solid alanine [28], polystyrene, and polysilanes [29], [30]. However, [31] reported similar effects on the elongation to break in Ultem and Kapton irradiated by 3 MeV protons, 2 MeV electrons, or gamma-rays.…”
Section: Radiation-induced Degradation In Polymersmentioning
confidence: 99%
“…We have reported the radiation induced reactions in -conjugated polymers and the dependence of reaction processes on the nature of radiation sources: LET (linear energy transfer: energy deposition rate of incident particles per unit length). [42][43][44] The polymers seem to be crosslinked by high LET radiations including high energy charged particles, despite of predominant main chain scission reactions observed for low LET radiation. The difference in radiation induced reactions was ascribed to a variation of density of reactive intermediates.…”
Section: -4mentioning
confidence: 99%
“…[45][46][47] Polysilanes were cross-linked by high LET radiations including high energy charged particles, despite of predominant main chain scission reactions observed for low LET radiations or photons. 42,43 It should be noted that the cross-linking reactions depended strongly on the density of neutral reactive intermediates: silyl radicals, 80 and the reactions seemed to occur within a nm-scaled cylindrical space along an incident particle trajectory where the intermediates distributed densely and non-homogeneously. [45][46][47] This process will potentially give a insoluble ''nano-gel'' along each corresponding particle, and produce wire-like 1D-nanostructures via isolation of ''nano-gel'' on a substrate by removing soluble uncross-linked parts.…”
Section: Intrinsic Mobility Of Charge Carriers Along -Conjugated Chainsmentioning
confidence: 99%
“…For example, three dimensional structures, such as overhang structures and bridges, were fabricated by proton beam with different energies and the development at one time, known as Proton Beam Writing (PBW) [1][2][3][4][5][6][7][8][9]. In the case of low-fluence irradiation of heavy ion beams, known as Single Particle Nanofabrication Technique (SPNT) [10][11][12][13][14][15][16][17][18], long nanowires with the length of micron order can be formed without post-exposure baking. However, there are some problems that the nanowires were collapsed, adhered to the substrate, cohered randomly, or flowed away through the development and the drying process.…”
Section: Introductionmentioning
confidence: 99%